Stereo- and substituent-enabled divergent synthesis of 5, 6-spiroketal analogs of avermectin containing a triazole function. Issue 32 (9th August 2017) - Yamada, Takeshi; Horimatsu, Yuki; Hirose, Tomoyasu; Sugawara, Akihiro; Ōmura, Satoshi; Sunazuka, Toshiaki
Graphical abstract: Highlights: Divergent synthesis and nematocidal activity of avermectin analogs. Stereodivergent 5, 6-spirocyclization. One-pot triazole formation between three TMS-alkynes and organic azides. Alkyne analogs showed comparable nematocidal activity to that of ivermectin. Abstract: Stereo-divergent construction of a 5, 6-spiroketal moiety, together with an efficient strategy to access various avermectin analogs containing a triazole group, has been accomplished. In the spirocyclization event, a C21 R spiroketal product was selectively obtained using Zn(OTf)2 as a Lewis acid. Conversely, use of Sc(OTf)3 afforded a C21S spiroketal compound as the major product. One pot triazole formation between three TMS-alkyne substrates and organic azides effectively provided the corresponding anti-triazole products. This strategy generates stereochemical and substituent diversity among avermectin analogs. Some of the 5, 6-spiroketal analogs showed anti-nematodal activity comparable to ivermectin.